Fundamentals of Shallow Water Acoustics - Katsnelson, Boris; Petnikov, Valery; Lynch, James; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Shallow water acoustics (SWA), the study of how low and medium frequency sound propagates and scatters on the continental shelves of the world's oceans, has both technical interest and a large number of practical applications. Technically, shallow water poses an interesting medium for the study of acoustic scattering, inverse theory, and propagation physics in a complicated oceanic waveguide. Practically, shallow water acoustics has interest for geophysical exploration, marine mammal studies, and naval applications. Additionally, one notes the very interdisciplinary nature of shallow water acoustics, including acoustical physics, physical oceanography, marine geology, and marine biology. In this specialized volume, the authors, all of whom have extensive at-sea experience in U.S. and Russian research efforts, have tried to summarize the main experimental, theoretical, and computational results in shallow water acoustics, with an emphasis on providing physical insight into the topics presented.
Preface -- 1. What is Shallow Water Acoustics? -- 2. Coastal Oceanography, Geology, and Biology -- 3. Foundations of the Theory of the Propagation of Sound -- 4. Examples Illustrating the Characteristics of Waveguide Propagation -- 5. Sound Field in Shallow Water with Random Inhomogeneities -- 6. Low Frequency Bottom Reverberation in Shallow Water -- 7. The Inverse Problem -- 8. Signal Processing -- 9. Noise Field in Shallow Water -- 10. Equipment for Shallow Water Acoustics and Experimental Considerations -- 11. The Future -- Appendix A. Waves and Signals -- Appendix B. Modal Decomposition of the Sound Field From the Point Source Green Function -- Appendix C. Mode Coupling Equations -- Appendix D. Empirical Orthogonal Functions -- Appendix E. Scattering At Localized Inhomogeneities in the Waveguide-Approximate Description -- Appendix F. Reflection of A Plane Wave From A Half Space -- Main Provisional Notation -- Bibliography and References -- List of Acronyms -- Index.
Keywords: Physics; Oceanography; Acoustics; Marine Sciences; Physics; Acoustics; Oceanography; Marine & Freshwater Sciences